DIFFERENCES OF MATERNAL SOCIODEMOGRAPHIC CHARACTERISTICS WITH SPONTANEOUS PRETERM BIRTH AMONG HOSPITALS IN INDONESIA: A COMPARATIVE STUDY - Sriyana Herman; Budi Santoso; Hermanto Tri Djoewono (Public Health of Indonesia)
Background: Maternal sociodemographic characteristics can be used to prevent preterm birth. Objective: To identify differences in maternal sociodemographic characteristics with spontaneous preterm birth among hospitals in East Java, Indonesia. Methods: This was a descriptive study with comparative design in 134 mothers who experienced preterm birth at eight hospitals. Data were analyzed using Independent samples t-test. Result: Sixteen variables were significantly different in maternal sociodemographic characteristics with spontaneous preterm birth among eight hospitals, namely: gestational age (CI 95%:10.97-0.02, p <0.049), maternal age (CI 95%:0.46-11.03, p <0.035), smoking (CI 95%:9.98-19.01 p <0.001), Edinburgh Postnatal Distress Scale (EPDS) (CI 95%:6.90-17.09, p <0.001), the fetus mobile (CI 95%:2.41-11.58, p <0.006), the number of visits during pregnancy (CI 95%:5.63-14.36, p <0.001), history of premature (CI 95%:7.76-15.73, p <0.001), history of disease (CI 95%:9.02-18.97, p <0.001), history of abortion (CI 95%:9.34-18.65, p <0.000), height (CI 95%:9.66-18.83, p <0.001), BMI (CI 95%:0.75-11.74, p <0.029), Mid Upper Arm Circumference (MUAC) (CI 95%:2.53-12.96, p <0.007), periodontal infection by (CI 95%:6.04-15.45, p <0.001), bleeding in young and old pregnancy (CI 95%:7.71-17.28, p <0.001), anemia status (CI 95%:2.30-10.19, p <0.004) and BV status (CI95%:9.05-20.45, p <0.001).